EFFECT OF THICKNESS ON THE BEARING STRENGTH AND SECONDARY BENDING OF COUNTERSUNK COMPOSITE JOINT - HAO MengJun; ZHANG Ming (Jixie qiangdu)
Joints are critical elements in designing safe and efficient vehicle structures made from composites. Aim to singlelap,single-bolt countersunk composites joints,a finite element model（ FEM） of the joint is established. Effectiveness of the FE model is verified. Based on this,the effects of laminate thickness on the secondary bending and bearing strength are studied. The numerical results demonstrate that the bearing strength of thin and thick composite joint are almost identical. In addition,the secondary bending effect of the thin composite joint is the least obvious when the bearing failure. The failure characteristics found in our study has direct implications when design of weight-saving of advanced composite structures.